Insights into the Allosteric Regulation of Human Hsp90 Revealed by NMR Spectroscopy - Tjaša Goričan; Simona Golič Grdadolnik (Biomolecules)
Human heat shock protein 90 (Hsp90) is one of the most important chaperones that play a role in the late stages of protein folding. Errors in the process of the chaperone cycle can lead to diseases such as cancer and neurodegenerative diseases. Therefore, the activity of Hsp90 must be carefully regulated. One of the possibilities is allosteric regulation by its natural allosteric modulators—nucleotides, co-chaperones and client proteins—and synthetic small-molecule allosteric modulators, such as those targeting the middle domain or the C-terminal domain (CTD) of Hsp90. Since no experimentally determined structure of a small-molecule allosteric modulator bound to the CTD of human Hsp90 has yet been obtained, the challenge for a structure-based design of allosteric modulators remains. Solution nuclear magnetic resonance (NMR) spectroscopy could be utilized to overcome these problems. The main aim of this review article is to discuss how solution NMR techniques, especially protein-based, and the advanced isotope labeling of proteins have been used to investigate the allosteric regulation of the cytosolic isoforms of human Hsp90 with allosteric modulators. This article provides the basis for planning future NMR experiments, with the aim of gaining insights into allosteric sites and the mechanisms of allosteric regulation.